2023
DOI: 10.3390/ma16134574
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Impact of Layer Height and Annealing Parameters on the Tensile Strength and Dimensional Accuracy of FDM 3D Printed Parts

Jelena R. Stojković,
Rajko Turudija,
Nikola Vitković
et al.

Abstract: This study investigates the impact of annealing time, temperature, and layer height on the tensile strength and dimensional change of three 3D printing materials (PLA, PETG, and carbon fiber-reinforced PETG). Samples with varying layer heights (0.1 mm, 0.2 mm, and 0.3 mm) were annealed at temperatures ranging from 60–100 °C for 30, 60, and 90 min. Tensile tests were conducted, and regression models were developed to analyze the effects of these parameters on tensile strength. The models exhibited high accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…In this research, an increased layer height led to a smaller number of layers, which was observed to contribute to the thickness deviation. Stojkovic et al [ 59 ] also reported that layer height has a clear impact on the dimensional accuracy of MEX 3D‐printed parts, although the specific influence may vary depending on the material and other printing parameters. However, the individual effects of printing temperature and layer height on the thickness deviation are not clear in Figure 4A as multiple factors can influence dimensional inaccuracy simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…In this research, an increased layer height led to a smaller number of layers, which was observed to contribute to the thickness deviation. Stojkovic et al [ 59 ] also reported that layer height has a clear impact on the dimensional accuracy of MEX 3D‐printed parts, although the specific influence may vary depending on the material and other printing parameters. However, the individual effects of printing temperature and layer height on the thickness deviation are not clear in Figure 4A as multiple factors can influence dimensional inaccuracy simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…PET-G samples (hollow and solid), 5-15 mm diameter, were made with FDM, varying temp (220°C, 240°C) and speed (30 mm/s, 40 mm/s) to assess dimensional accuracy, highlighting temperature's impact. Stojković et al [13] focused on PLA, PETG, and carbon fiber-reinforced PETG in 3D printing. They investigated annealing's impact on tensile strength and dimensions, varying layer heights (0.1 mm, 0.2 mm, 0.3 mm), and annealing conditions (60-100°C, 30-90 min).…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in awareness of environmentally friendly materials, TPE material plays a very important role in replacing vulcanized rubber and flexible polyvinyl chloride [2]. PLA performs best at 0.1 mm/60 min/90 °C, while PETG and PETGCF achieve optimal strength [3]. To improve the mechanical properties and surface quality of PLA FFF parts, enhancing surface and forming quality [4] expanding additive manufacturing for sacrificial cladding affects structural parameters, causing higher peak forces [5].…”
Section: Introductionmentioning
confidence: 99%